Rethinking Conceptual Sufism: A Synthesis of Islamic Spirituality, Asceticism, and Mysticism - Meis Al-Kaisi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2021)
Far from being a school or a sect, Sufism is an ideology, a mode of life, a set of principles, and a ‘faith in practice.’ Sufism has been addressed and presented by scholars countless times. It has been primarily defined as either Islamic mysticism or as the spiritual dimension of Islam. Yet, as much as mysticism is ineffable as much as the published research is full of tangled definitions that only scholars can comprehend. The traditional approach to the study of Sufism makes the topic burdensome and mentally unattainable to the learned public. This article explains Sufism without using complex terminology or intense presentations of mystical states and stations. It is a scholarly attempt that is ultimately designed to provide a straightforward definition of Sufism. It presents Sufism in a three-fold manner, as a synthesis of three Islamic principles: Islamic spirituality, asceticism, and mysticism. Each of the three dimensions is explained in an Islamic context to demonstrate the validity of the Sufi trends as being purely Islamic. Spirituality, asceticism, and mysticism are all discussed within the frame of Tradition, that is, the Quran and the Sunna of the Prophet Muhammad.